2021
DOI: 10.7759/cureus.16978
|View full text |Cite
|
Sign up to set email alerts
|

Non-melanoma Skin Cancers in Patients on Hydroxyurea for Philadelphia Chromosome-Negative Myeloproliferative Neoplasms: A Systematic Review

Abstract: Hydroxyurea (HU) or hydroxycarbamide is a cytotoxic antimetabolite widely used to treat Philadelphia chromosome-negative Myeloproliferative Neoplasms (Ph-MPN) like Polycythemia Vera (PV), Essential Thrombocythemia (ET), and Primary Myelofibrosis (PMF). Patients with Ph-MPN are at an increased risk of Non-melanoma skin cancers (NMSC). The cause of this finding remains uncertain. In this systematic review, we would like to know if chronic use of HU in this population is responsible for the sudden onset of NMSC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…A potential clinical and histopathological pitfall is the presence of numerous degranulated mast cells in skin biopsies of MPN patients with itchy lesions, which should not be misdiagnosed as mastocytosis 77 . Concerning therapy‐related lesions, treatment with hydroxyurea is known to produce skin lesions such as ulcers, actinic keratosis/squamous cell carcinoma, and skin and nail hyperpigmentation in around 5% of patients, which are clinically and histopathologically different from neoplastic cutaneous involvement in MPNs 78 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential clinical and histopathological pitfall is the presence of numerous degranulated mast cells in skin biopsies of MPN patients with itchy lesions, which should not be misdiagnosed as mastocytosis 77 . Concerning therapy‐related lesions, treatment with hydroxyurea is known to produce skin lesions such as ulcers, actinic keratosis/squamous cell carcinoma, and skin and nail hyperpigmentation in around 5% of patients, which are clinically and histopathologically different from neoplastic cutaneous involvement in MPNs 78 …”
Section: Discussionmentioning
confidence: 99%
“…77 Concerning therapy-related lesions, treatment with hydroxyurea is known to produce skin lesions such as ulcers, actinic keratosis/ squamous cell carcinoma, and skin and nail hyperpigmentation in around 5% of patients, which are clinically and histopathologically different from neoplastic cutaneous involvement in MPNs. 78…”
Section: Differential Diagnosis Of Skin Lesions In Mpn Patientsmentioning
confidence: 99%
“…Among patients treated with ruxolitinib in JUMP, NMSCs were the most common secondary malignancies and were reported in 2.7% of patients treated with ruxolitinib [ 7 ]. By comparison, a recent systematic review of patients with MPNs treated with HU in observational studies reported NMSC rates of 0.29% (10/3411 patients in a retrospective Italian study; median age, ≈63 years), 9.6% (127/1316 in an Italian case-control study; median HU exposure, 3 years), 13.6% (9/66 in a retrospective Czech study; median age, 64 years), and 34.2% (51/149 patients in a retrospective Australian study; median HU exposure, 4 years; median age, 66 years) [ 47 ]. Finally, in a noninterventional postauthorization safety study of 462 patients with MF that included prevalent or new users of ruxolitinib, a nonsignificant trend toward increased risk of NMSC with increasing ruxolitinib exposure was observed (hazard ratio [HR] corresponding to risk with each additional year of ruxolitinib, 1.2 [95% CI 0.9, 1.6]) [ 16 ].…”
Section: Risk Of Serious Aesmentioning
confidence: 99%
“…In fact, it increases the number of DNA breaks, causing the strands to remain open longer, and decreases the DNA polymerase activity, thereby slowing the polymerization rate at the repair sites [ 13 , 14 ]. Furthermore, HU and exposure to UV radiation play a combined role in skin cancers onset; in fact, UV-B rays promote the proliferation of TP53 mutant keratinocytes (seen in the dermo-epidermal junction and hair follicles) and enable them to colonize the adjacent compartment [ 15 , 16 ]. In the basal layer of the epidermis, the high keratinocyte turnover with HU impaired DNA synthesis and repair are the causes of skin tumors onset [ 61 ].…”
Section: Possible Links Between Mpns and Scmentioning
confidence: 99%